London's food policy: Leveraging the policy sub-system, programme and plan. (August 2021) - Parsons, Kelly; Lang, Tim; Barling, David
Highlights: London's metropolis-wide food policy activities and actors are described. The concept of institutions as policy-structuring forces is applied. Enablers of and constraints on London's food policy are examined. A heuristic: sub-system, programme and plan, within wider government structures, is proposed. Re-balancing of national-local powers for food systems transformation is explored. Abstract: This article explores the spaces for, and boundaries to, London's food policy. Leveraging the concept of institutions as policy-structuring forces, it positions immediate policymaking capacity and potential as delineated by broader historical, social and legislative institutions. Using new data, the findings identify structuring effects including: the strategic force of different policy areas; the Mayor's remit and interests; relationships between the London authority and the boroughs, as well as in relation to the national level; and requirements for integration. Within the metropolitan government space, distinguishing between the food policy sub-system, programme and plan provides a conceptual device to understand how food policy in London extends beyond its limited direct levers and resources – reflecting and responding to the city's longstanding complicated and multi-tiered governance. Food policy is enabled through a sub-system consisting of a set of dedicated food governance structures and mechanisms – a permanent team of staff, plus policy networks, advisors and street-level implementers – which utilise different modes of policy integration to bolster the programme of activities around food. A new cross-cutting food plan – the London Food Strategy – was developed in 2018 to coordinate these different actors and activities. The case study enables critical reflection on the potential for urban food policy to address a range of food systems outcomes. While some harder policy interventions are possible, there remains a multi-level disconnect in policy authority between the local borough, metropolitan and national levels. There are constraints on how far transformation can take place, raising questions about the re-balancing of national-local power sharing which will be required for a more coherent and transformative approach.